COUNTERACT RADICALISM AND BRING UP BHINNEKA TUNGGAL IKA (REFLECTION OF QS AL-HUJURAAT: 13) - Nia, Krista; Purnomo, Agus (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The purpose of this study is to know the students' understanding of Radicalism and the value of diversity through the Pancasila Education and Citizenship Education Course at the State University of Malang. Pancasila Education basically provides insight to students about the diversity of existing values in Pancasila. One of the values of diversity is anti-radicalism. This value is very necessary to be reinforced in view of the many cases of radicalism involving student groups. The value of diversity is also found in QS Al-Hujuraat verse 13. This research is a descriptive qualitative research through literature study and questionnaire distribution through googleform s well as researching the text of messages from the value of the Quran and Pancasila. In conducting the analysis, the author collects the material and is described, interpreted, compared to the similarities and differences with the particular phenomenon raised, then draws conclusions. The expected outcome of this study is the building of a model to provide understanding to students that 1). Multiculturalism is the wisdom to see fundamental diversity as a fundamental reality in social life 2). The role of Pancasila as a philosophical paradigm should be giving awareness that fanaticism will only provide insurmountable problems, especially in terms of ethical, religious, and cultural values. Pancasila Education and Citizenship Education is one effort to be done so that radicalism is not widespread and the spirit of diversity is greater 3).